Ararem, Abderrahmane . Slamene , Hocine . Dendene ,Omar. Non-destructive multielement analysis of airborne particles by instrumental neutron activation analysis - Ararem Abderrahmane-Slamene Hocine (University of Eloued جامعة الوادي, 2024)
Instrumental neutron activation analysis (INAA) was used for the determination of the elemental composition of aerosol samples. Two samples of air of approximately 20 m3 each one were collected of the atmosphere around the Es-Salam research reactor site in Algeria. The irradiation of the samples and reference materials was carried out during 30 s for the elements of short half-life and 06 h for the elements of medium and long half-life with a thermal neutrons flux of 1.12 1013 and 6.88 1013 n/cm²s respectively. Ge(Hp) -spectrometry made it possible to determine fifteen elements (Al, Cl, Mn, Ca, Cd, Br, La, Fe, Nd, Ce, Hg, Cr, Hf, Sb and Zn). The obtained results for the used reference materials almost perfectly match its certified values (Zscore<2).
Article
Keywords: Trace elements; airborne particles; Neutron activation analysis; Metals pollution.